Evaluating atmospheric mercury (Hg) uptake by vegetation in a chemistry-transport model. Issue 9 (29th April 2022) - Feinberg, Aryeh; Dlamini, Thandolwethu; Jiskra, Martin; Shah, Viral; Selin, Noelle E.
Abstract : We study the uptake of atmospheric mercury by vegetation in a chemical transport model and available observations. Due to the importance of this sink in the global mercury cycle, perturbations to forested areas can elevate mercury risks. Abstract : Mercury (Hg), a neurotoxic heavy metal, is transferred to marine and terrestrial ecosystems through atmospheric transport. Recent studies have highlighted the role of vegetation uptake as a sink for atmospheric elemental mercury (Hg 0 ) and a source of Hg to soils. However, the global magnitude of the Hg 0 vegetation uptake flux is highly uncertain, with estimates ranging 1000–4000 Mg per year. To constrain this sink, we compare simulations in the chemical transport model GEOS-Chem with a compiled database of litterfall, throughfall, and flux tower measurements from 93 forested sites. The prior version of GEOS-Chem predicts median Hg 0 dry deposition velocities similar to litterfall measurements from Northern hemisphere temperate and boreal forests (∼0.03 cm s −1 ), yet it underestimates measurements from a flux tower study (0.04 cm s −1 vs. 0.07 cm s −1 ) and Amazon litterfall (0.05 cm s −1 vs. 0.17 cm s −1 ). After revising the Hg 0 reactivity within the dry deposition parametrization to match flux tower and Amazon measurements, GEOS-Chem displays improved agreement with the seasonality of atmospheric Hg 0 observations in the Northern midlatitudes. Additionally, the modelled bias in Hg 0 concentrations in South America decreases from +0.21 ng m −3 to +0.05 ng m −3 . We calculate a global flux of Hg 0 dry deposition to land of 2276 Mg per year, approximately double previous model estimates. The Amazon rainforest contributes 29% of the total Hg 0 land sink, yet continued deforestation and climate change threatens the rainforest's stability and thus its role as an important Hg sink. In an illustrative worst-case scenario where the Amazon is completely converted to savannah, GEOS-Chem predicts that an additional 283 Mg Hg per year would deposit to the ocean, where it can bioaccumulate in the marine food chain. Biosphere–atmosphere interactions thus play a crucial role in global Hg cycling and should be considered in assessments of future Hg pollution.